Habitat suitability prediction model of wildlife at Royal Belum State Park using geographical information system - Nor Liyana, M. (Association for Geoinformation Technology, 2016)
Human mobility in Royal Belum State Park affected the salt lick, which is an important area for animal nutrient supply. Salt lick area affected the temperament of the wild animals as the salt lick is considered as one of their habitats whereby the source partition of food specialized for animal dietary intake are available. This study aims to predict the habitat suitability for protected species in Royal Belum State Park, Perak, Malaysia. The investigation includes identifying tracks of wildlife by camera traps to observe the activity patterns of the animals. AU information derived from the salt licks location and topographic maps have been prepared to create the thematic layers. Spatial prediction models for wildlife conservation purpose are developed by identifying the red areas. This suitability model can be used for animal protection plan in future study.